Can we calculate the inverse of the reciprocal of a function in terms of the function's inverse?


Now we need to calculate $g^{-1}(x)$ in terms of $f^{-1}(x)$


$x=f(y)\implies y=f^{-1}(x)$

$f(y)=\cfrac {1}{g(y)}$

$\implies f(y)=\cfrac 1{g\big(f^{-1}(x)\big)}$

$\implies g\big(f^{-1}(x)\big)=\cfrac 1{f(y)}=\cfrac 1x$

$\implies g\big(f^{-1}(\cfrac 1x)\big)=x$

$\implies g^{-1}(x)=f^{-1}(\cfrac 1x)$

Not exactly what you want.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.